2013
DOI: 10.5539/ijbm.v8n24p117
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ Political Connections and Compliance with Board of Directors Regulations: The Case of S&P/Tsx 300 Companies

Abstract: Further to the various scandals that shook North-American markets in the early 2000s, Canada reacted in 2004 and 2005 by changing its regulations on the governance practices of listed companies. Faccio (2006) and other authors have argued that politically connected companies can have less regulatory oversight than unconnected firms. This affirmation raises an issue that this article attempts to solve, i.e., whether politically connected Canadian companies are less compliant with regulatory requirements on gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…1;2015 In view of the fact that US listing seems to influence firm compliance with board regulations, there is a very significant difference between US listed and unlisted firms in terms of their compliance with board regulations. This finding is consistent with past studies (Khemakhem & Dicko, 2013) which showed that US corporate governance regulations are more stringent than Canadian regulations. According to ANOVA results, there is a significant difference between politically connected and non-connected firms in terms of financial performance (measured by ROA, ROE and MTB).…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 83%
See 1 more Smart Citation
“…1;2015 In view of the fact that US listing seems to influence firm compliance with board regulations, there is a very significant difference between US listed and unlisted firms in terms of their compliance with board regulations. This finding is consistent with past studies (Khemakhem & Dicko, 2013) which showed that US corporate governance regulations are more stringent than Canadian regulations. According to ANOVA results, there is a significant difference between politically connected and non-connected firms in terms of financial performance (measured by ROA, ROE and MTB).…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 83%
“…This finding corroborates the results of Khemakhem and Dicko's study (2013) of a similar Canadian sample. Khemakhem and Dicko (2013) found that US market listing influences Canadian firms' compliance with governance regulations in view of the greater stringency of US regulations. According to Table 4, no significant differences were found between politically connected vs. non-connected firms among those listed on the US market; in other words, being listed on the US market did not influence the firms' political connections behaviour.…”
Section: Political Connections and Compliance With Board Regulationsmentioning
confidence: 99%
“…The existence of such rules and codes should ensure due process and accountability in public procurement. However, given the resource-dependence and quid pro quo relationship existing between the political system and public sector firms (Khemakhem & Dicko, 2013;You & Du, 2013;Reich, 2009), as well as the pervasively negative and self-seeking nature of party politics (Roman, 2017(Roman, , 2014Wright, 2004), this study posits that supplier selection decisions will be associated with instrumental ethical work climates (the shared perception that organizational norms promote egoistic tendencies during 16 ANTECEDENTS OF SUPPLIER SELECTION DECISIONS decision-making), irrespective of the existence of 'strict' rules. Furthermore, given that organizational actors use their personal values and beliefs as a basis for making decisions (Roman, 2017(Roman, , 2014Sousa et al, 2003), it is not far-fetched to suggest that the instrumental ethical work climates prevalent in 'politicized' work environments such as most public sector firms (Roman, 2017) will be associated with self-enhancing personal values (also defined as the promotion of self-seeking tendencies and parochial personal interests).…”
Section: Antecedents Of Supplier Selection Decisionsmentioning
confidence: 99%
“…Since certain regulations in the US (e.g. on corporate governance) are more stringent than in Canada, Canadian companies behave differently when listed on US financial markets (Khemakhem & Dicko, 2013;Dicko & Khemakhem, 2015). We therefore decided to include this variable in our study, using a dummy variable valued at 1 if the company is listed on US markets and 0 otherwise.…”
Section: Control Variablesmentioning
confidence: 99%